Analysis of Shared Memory Priority Queues with Two Discard Levels. - Bergida, S.
Two-rate SLAs become increasingly popular in today's Internet, allowing a customer to save money by paying one price for committed traffic and a much lower price for additional traffic that is not guaranteed. These types of SLAs are suggested for all types of traffic from best effort to QoS constrained applications. In access networks, where these SLAs are prevalent, shared memory switches are a common feature of architecture. Thus, dimensioning and management of shared memory queues for multiple priorities, each with two levels of guarantees, becomes an interesting challenge. We present a simple analysis of a multipriority multi-discard-level system controlled by a buffer occupancy threshold policy aimed at assuring SLA compliance for conforming (i.e., committed) traffic, and performance maximization for nonconforming (i.e., excess) traffic. Our analysis shows how to calculate the different system parameters: total buffer size, threshold position, and offered load control performance for the committed and excess traffic. Our suggested design enables assuring high SLA compliance for conforming traffic and performance maximization for nonconforming traffic.
Keywords: Internet; QoS; SLA; Access networks; Additional traffic; Committed traffic; Multipriority multi-discard-level system; Shared memory switches; Shored memory priority queues analysis